Is the Ecosystem of Kolkata Sustainable?: Machine Learning Based Study on Air Quality Index - Dr. Biswajit Biswas; Sayantan Ghosh, (Indian Journal of Artificial Intelligence and Neural Networking (IJAINN), 2024)
Timely and accurate forecasting of Air Quality Index (AQI) helps the Industries to select suitable control of air pollution measures. It helps people to reduce exposure in pollution. In this present age Air quality Index is one of the burning issues in India. The air contaminations are harmful for our biological system and also for the climate. To keep up the best air quality cross the country different types of air toxins are estimated through the air quality measuring standards. The aim of this research work is modelling air quality of a location with respect to time with the help of Machine Learning (ML). The proposed and developed model was emphasizes particularly in Kolkata, capital of the state West Bengal in India and the findings have direct implications to build & maintain a sustainable ecosystem over there.